'Rising', 'hopeful', 'new': visualizing Africa in the age of globalization. (August 2014) - Nothias, Toussaint
This article focuses on covers published in British, French and US American news magazines between 2011 and 2013 as micro-textual cases that can shed light on the evolution of Africa's media image from Afro-pessimism to Afro-optimism. On the one hand, these depictions blend signifiers of modernity, positivity and 'Africanness'. On the other hand, these covers are a prime example of a visual style that favours symbolic representation and generic imagery. By combining a detailed analysis of textual material with interviews with media professionals, this article critically examines the ways in which Africa's difference is summoned and framed within a specific visual style. Although the article finds a significant amount of media self-reflexivity, it argues that this positive and reflexive trend should not be embraced as radically undermining Afro-pessimism. Instead, this way of visualizing Africa mainly contributes to the discursive (re)inscription of Africa's difference within a dominant discourse of globalized neoliberalism.